KATEGORIALE SAMLINGER: Eller hvordan man fik indført en vis orden i universet i det 18. århundredes - Jørgensen, Kirsten Winther (Tidsskriftet Antropologi, 2001)
Following the zoologists of eighteenthcentury Britain from the field to the study this article investigates how animals were categorised in the grand taxonomic systems of the day. The article analyses the epistemological, social and cosmological underpinnings of this particular kind of classificatory collections, showing both how the notions of specimens, species, genera, orders and classes of the taxonomic systems as well as the methods of categorisation were culturally framed, and how the categorisation of animals entailed a categorisation of humans well. The article hence deals with the categorial collections of eighteenth-century zoology from the vantage points of both a history of science and an anthropology of the “totemic” perspective.